From Shore to Mind: Maritime Science Literacy of Children in Early Childhood - Masliati, Tati; Nuryati, Nuryati; Mulhanah, Mulhanah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2025)
Indonesia, as a maritime nation, faces the challenge of low maritime science literacy among the younger generation, including in early childhood. This study aims to examine the potential, obstacles, and strategies for strengthening maritime science literacy in early childhood education institutions. The method used was a literature review by analyzing 30 references published between 2016 and 2024, including three journals by Nuryati. The results indicate that the integration of marine themes in early childhood education is still minimal due to limitations in media, curriculum, and teacher training. However, a thematic approach, the role of families, and marine-based media can be a solution to instill a scientific understanding of the ocean from an early age. This study recommends the need for national policies and cross-sectoral support so that maritime science literacy becomes an integral part of early childhood education.